STUDENTS PERCEPTION TOWARD DESCRIPTIVE REVIEW ACTIVITY ON EXTENSIVE READING CLASS OF ENGLISH DEPARTMENT OF WIDYA GAMA MAHAKAM UNIVERSITY - Widi Syahtia Pane (Pendas Mahakam : Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2022)
Reading is one of four skills that must be mastered for English as Foreign Language (EFL) learners. Extensive reading is one of class that students need to take to get bachelor degree in English Department of University of Widya Gama Mahakam Samarinda. Extensive reading goal is to create a fun reading for students, to boost their interest in reading especially English reading. In this academic year, the students of 2021 took their extensive reading class in pandemic era therefore they need to take this class through online proccess. This research aims to find out what is students’ feeling after/ whilst reading their favorite English books, novels and short stories in Extensive Reading class. The result reveals that most of students have positive perception towards this activity. Some difficulty faced by a few students in this activity are the difficulty to read the novel even thought this activity bring some positive effect to their study including learning about new vocabularies and motivating them to be independent in learning. They also hope that this descriptive review activity supports them in English reading and they also expect that they would have some other activities to engage fun environtment on their class.